Refractive Errors Among Medical Students - Karki, Poojyashree; Sijapati, Milesh J; Basnet, Pragya; Basnet, Anjila (Nepalese Medical Journal, 2018)
Introduction: Refractive errors are becoming a problem in many societies, with prevalence rates of myopia in many Asian urban countries reaching epidemic proportions. This study aims to determine the prevalence rates of various refractive errors among medical students of Kist Medical College Teaching Hospital, Nepal. Materials and Methods: Medical students were included in the study. Demographic data was obtained via questionnaires filled in by the students after taking informed verbal consent. Refractive error measurements were determined by dry retinoscopy and additional cycloplegic refraction as and when needed. Results: The prevalence rate of simple myopia was 64.81% and 3.7% had high myopia. Hyperopia (Hypermetropia) was present in 1.8% of the participants while overall astigmatism prevalence rate was 29.6% among medical students. Conclusion: Prevalence rates of myopia in medical students are found to be quite high. Conclusions: Prevalence rates of myopia in medical students are found to be quite high. Nepalese Medical Journal, vol.1, No. 1, 2018, page: 21-23